2017
DOI: 10.1007/s00109-017-1505-9
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-mediated enzyme replacement therapy targeting both lysosomal and cytoplasmic glycogen in Pompe disease

Abstract: Pompe disease is characterized by accumulation of both lysosomal and cytoplasmic glycogen primarily in skeletal and cardiac muscles. Mannose-6-phosphate receptor-mediated enzyme replacement therapy (ERT) with recombinant human acid α-glucosidase (rhGAA) targets the enzyme to lysosomes and thus is unable to digest cytoplasmic glycogen. Studies have shown that anti-DNA antibody 3E10 penetrates living cells and delivers Bcargo^proteins to the cytosol or nucleus via equilibrative nucleoside transporter ENT2. We sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…This antibody-enzyme fusion (AEF) strategy has proven successful for the replacement of a cytosolic enzyme and rescue of X-linked myotubular myopathy in mice (Lawlor et al, 2013). A Fab-GAA fusion has similar efficacy to reduce glycogen in Pompe mice with the additional advantage of targeting both lysosomal and cytosolic glycogen and is now in Phase 1/2 clinical trials (Valerion Therapeutics, 2016;Yi et al, 2017). Rather than utilizing the AEF platform to deliver a replacement enzyme, we generated an AEF designed to penetrate cells and degrade pathogenic LBs.…”
Section: Introductionmentioning
confidence: 99%
“…This antibody-enzyme fusion (AEF) strategy has proven successful for the replacement of a cytosolic enzyme and rescue of X-linked myotubular myopathy in mice (Lawlor et al, 2013). A Fab-GAA fusion has similar efficacy to reduce glycogen in Pompe mice with the additional advantage of targeting both lysosomal and cytosolic glycogen and is now in Phase 1/2 clinical trials (Valerion Therapeutics, 2016;Yi et al, 2017). Rather than utilizing the AEF platform to deliver a replacement enzyme, we generated an AEF designed to penetrate cells and degrade pathogenic LBs.…”
Section: Introductionmentioning
confidence: 99%
“…While the glycogen in some GSDs is of normal structure like in Pompe disease, other GSDs such as Cori disease and Andersen disease are characterized by polyglucosans, like LD (7). Two AEF drugs (VAL-0417 and Fab-GAA) have now been shown to target, respectively, cytosolic polyglucosan (the present study) and normal glycogen in both the cytosol and lysosome (47). These drugs could be repurposed and/or modified to target glycogen in other GSDs.…”
Section: Discussionmentioning
confidence: 63%
“…In the first study, the deficient lipid phosphatase myotubularin fused to an Fv fragment was delivered by intramuscular injection and improved muscle function in a mouse model of myotubular myopathy (46). In the second, a Fab fragment fused to GAA delivered intravenously reduced glycogen load and alleviated pathology in GAA-deficient mice (47). These two studies illustrate that enzyme replacement therapy, which can be problematic for cytosolic enzymes, can be enhanced by fusion of the replacement enzyme with a cell-penetrating antibody fragment.…”
Section: Discussionmentioning
confidence: 99%
“…This monoclonal anti-DNA antibody were shown to penetrate living cells and move to the nucleus through the equilibrative nucleoside transporter 2 (ENT2) [113][114][115]. Experiments in cultured L6 myoblasts and fibroblasts derived from Pompe disease patients as well as in vivo studies in KO mice suggested a potential benefit of this fusion protein [116]. However, in our experience, VAL-1221 in KO mice did not show any improvement in muscle glycogen content (unpublished data).…”
Section: Next-generation Ertmentioning
confidence: 80%